Enacting emotional labour in consultancy work: Playing with liminality and navigating power dynamics. Issue 3 (July 2020) - Iszatt-White, Marian; Lenney, Peter
While theoretical understanding of professional emotional labour has developed in recent years, methodological issues with capturing its practice mean that understanding of how professional emotional labour is enacted remains relatively limited. The current study utilises memory work to surface potentially unacknowledged meanings associated with the remembered performance of professional emotional labour as a proxy for the psychological access required to demonstrate dissonance between felt and displayed emotions. The article uses an emotionally charged feedback meeting between a management consultant and their client as an opportune context for surfacing the enactment of professional emotional labour. The combined memory work data – consisting of original meeting recordings and a parallel commentary developed in discussion with the consultant – are analysed through a Goffmanian lens in order to theorise role positioning as a tool of enacting professional emotional labour. A model is proposed that maps the roles adopted against the dimensions of playing with liminality and navigating power dynamics. We suggest the potential transferability of these findings to other situations of liminality and their relevance for management learning interventions.